2003
DOI: 10.1007/s00775-002-0420-9
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)-phenolate complexes as models of the reduced active site of galactose oxidase: synthesis, characterization, and O2 reactivity

Abstract: The Cu(I)-phenolate complexes (1)LCu and (2)LCu and the Cu(I)-phenol complex [H(2)LCu(CNC(6)H(3)Me(2))]BArF(4) were prepared and structurally characterized by X-ray crystallography, where (1)L(-) and (2)L(-) are ligands comprised of a 2,4-di- tert-butylphenolate linked to 1-isopropyl-1,5-diazacyclooctane or 1,4-diisopropyl-1,4,7-triazacyclononane, respectively. The reduced galactose oxidase (GAO) structural models (1)LCu and (2)LCu were found to be highly reactive with O(2), and through combined stopped-flow k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 68 publications
3
45
0
2
Order By: Relevance
“…Such species have been found in the reactions of O 2 with heme proteins and models (6,7) as well as with one copper enzyme (8) and several synthetic copper and nickel complexes (9)(10)(11)(12)(13)(14)(15)(16). Such species have also been invoked in the mechanisms for nonheme iron enzymes, but only indirect evidence has been obtained to date (39)(40)(41).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such species have been found in the reactions of O 2 with heme proteins and models (6,7) as well as with one copper enzyme (8) and several synthetic copper and nickel complexes (9)(10)(11)(12)(13)(14)(15)(16). Such species have also been invoked in the mechanisms for nonheme iron enzymes, but only indirect evidence has been obtained to date (39)(40)(41).…”
Section: Discussionmentioning
confidence: 98%
“…Crystallographic evidence for an analogous formulation has also recently been reported for a copper enzyme peptidylglycine ␣-hydroxylating monooxygenase (PHM) (8). Furthermore, synthetic copper(I) and nickel(I) complexes react with O 2 to give rise to copper and nickel superoxo species (9)(10)(11)(12)(13)(14)(15)(16) 2 was prepared by using the same procedure in the presence of 10 eq of D 2 O. All manipulations with complex 1 and solutions thereof were carried out under inert atmosphere by using a glovebox filled with nitrogen.…”
mentioning
confidence: 99%
“…Our own interests in this area were piqued by recent work of Jazdzewski et al [30], who reported the synthesis of a 1:1 Cu-O 2 galactose oxidase model complex 6 supported by a ligand composed of a 2,4-di-tert-butylphenolate linked at N1 to a 4,7-diisopropyl-1,4,7-triazacyclononane. A crystal structure was not obtained for 6.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of the geometry of 6 was carried out at the DFT level for both the singlet and the triplet electronic states, although experiment is unambiguous in establishing the singlet as the ground state on the basis of the absence of an electron-spin-resonance spectrum [30]. The triplet state is found to have a single minimum-energy structure and that structure coordinates O 2 in an end-on fashion [ 3 6(g 1 ), Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation